ACOD1-mediated lysosomal membrane permeabilization contributes to Mycobacterium tuberculosis –induced macrophage death - Ziwei Yang; Li Zhang; Samantha Ottavi; Jacob B. Geri; Andrew Perkowski; Xiuju Jiang; Daniel Pfau; Ruslana Bryk; Jeffrey Aubé; Matthew Zimmerman; Véronique Dartois; Carl Nathan (Proceedings of the National Academy of Sciences, 2025)
Mycobacterium tuberculosis (Mtb) primarily infects macrophages. In vitro without antibiotics, wild-type Mtb hastens death of the macrophages, but the processes leading to rapid cell death are not well understood. Our earlier work indicated that the death of Mtb-infected mouse macrophages in vitro is markedly exacerbated by induction of interferon-β (IFN-β) [L. Zhang et al., J. Exp. Med. 18 , e20200887 (2021)]. Here, we identified a key downstream response to IFN-β in the context of Mtb infection as the massive induction of cis-aconitate decarboxylase (ACOD1), not only in its canonical subcellular localization in mitochondria but also in the cytosol, where it bound to the lysosome-stabilizing protein HSP70. ACOD1’s product, itaconate, protected Mtb-infected macrophages. However, the contrasting and predominant effect of high-level ACOD1 expression was to act in a noncatalytic manner to promote HSP70’s degradation, leading to lysosomal membrane permeabilization (LMP). Mtb-induced macrophage death was markedly diminished by inhibitors of cysteine proteases, consistent with lysosome-mediated cell death. Neither ACOD1 inhibitors nor cysteine protease inhibitors are suitable for potential host-directed therapy (HDT) of tuberculosis. Instead, this work directs attention to how ACOD1 acts nonenzymatically to promote the degradation of HSP70.